Significance of Cultural Variables - Richman, Barry M. (Academy of Management Journal, 1965)
The article addresses the foundations of effective management, which some believe to be based on universal principles and others believe are culture-bound. The article defines some of the obstacles to studying this issue, raises vital questions such as the transferability of American business practices to other countries or cultures, and identifies and categorizes significant cultural constraints that have an impact on management, including sociological and educational constraints and their relationship to management processes. The author presents some thoughts on research methodology as it relates to cultural norms and management practices in international business management.